2015
DOI: 10.1149/2.0591512jes
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Electrolyte Inventory and Lifetime of HT-PEFC by Accelerated Stress Testing

Abstract: Phosphoric acid electrolyte evaporation in a polybenzimidazole based high temperature polymer electrolyte fuel cell is analyzed as a function of reactant gas stoichiometry and temperature. Based on these results a phosphoric acid vapor pressure curve is derived to predict the fuel cell liftetime with respect to electrolyte inventory. The predicted fuel cell life was validated by means of an accelerated stress test. Additionally, the correlation between electrolyte inventory and fuel cell performance was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 28 publications
3
38
2
Order By: Relevance
“…In addition, it is evident that the acid-loss rate depends also on the current density, even for samples that have been operated with approximately equal gas-flow rates. This observation is highly interesting because it directly contradicts the results by Eberhardt et al 23 who concluded that the acid-loss rate, when normalized in…”
contrasting
confidence: 65%
See 2 more Smart Citations
“…In addition, it is evident that the acid-loss rate depends also on the current density, even for samples that have been operated with approximately equal gas-flow rates. This observation is highly interesting because it directly contradicts the results by Eberhardt et al 23 who concluded that the acid-loss rate, when normalized in…”
contrasting
confidence: 65%
“…Instead, we might ascribe the observation to decreasing ECSA due to loss of three-phase-boundary regions as a consequential secondary effect of severe acid loss whereby parts of the electrodes are rendered depleted of ion conducting phase. 23,37,38 While acid loss from the catalyst layer will also result in increased resistance, there should be no linear dependence on current in this case, so the effect should contribute neither to the ir-curves of Figure 2c nor to the ASR dependence shown in Figure 2d. However, the separation of ohmic and non-ohmic contributions by Equation 1 is a quite crude technique, and influence from some apparently linear contributions from the catalyst layer cannot be dismissed entirely.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…19 For example, the PA leaching rate at the cathode at 190 °C has been found to be about an order of magnitude higher than at 160 °C. 6,20 As a result, the durability data reported in the literature at 190-200 °C do not extend to much more than a few hundred hours of operation. 3,6,9 Increasing the operating temperature from 160 to 200 o C is, however, strongly beneficial due to further improved catalyst kinetics and fuel impurity tolerance in combination with better possibilities for thermal integration with fuel processing units.…”
mentioning
confidence: 93%
“…reported a 90 % loss of phosphoric acid in a fuel cell operated at 190 o C under a high gas flow rate [19].…”
Section: Introductionmentioning
confidence: 99%